Analyzing the Impact of Labor Force and Unemployment on Poverty Rates in Gowa District - Ua, A. Nur Achsanuddin; Rusdi, Muh.; Maulana, Fajar (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study aims to analyze the influence of labor force participation and unemployment on poverty rates in Gowa Regency, Indonesia. Employing a quantitative research design, the study utilizes time series data from 2014 to 2023, collected through observation and documentation techniques. The data were analyzed using multiple linear regression with the assistance of SPSS version 2.5. The findings reveal that labor force participation has a negative but statistically insignificant effect on poverty rates. This is evidenced by a t-value of -1.120, which is lower than the critical value of 1.894, and a significance level of 0.300 (p > 0.05). These results suggest that while higher labor participation may contribute to reducing poverty, the relationship is not statistically significant. Additionally, unemployment is found to have a positive but similarly insignificant effect on poverty, with a t-value of 0.010 and a significance level of 0.992 (p > 0.05). These findings indicate that changes in labor force participation and unemployment rates do not have a significant direct impact on poverty levels in the region. The study contributes to the discourse on labor market dynamics and socioeconomic development, providing empirical evidence for policymakers in designing effective poverty alleviation strategies